Quality of Childcare Influences Children's Attentiveness and Emotional Regulation at School Entry - Zubrick, Stephen; Lynch, John; Sawyer, Michael; Mittinty, Murthy; Sawyer, Alyssa; Gialamas, Angela (My University, 2014)
Objective: To examine the association between domain-specific qualities of formal childcare at age 2-3 years and children's task attentiveness and emotional regulation at age 4-5 and 6-7 years. Study design: We used data from the Longitudinal Study of Australian Children (n = 1038). Three domain-specific aspects of childcare quality were assessed: provider and program characteristics of care, activities in childcare, and carer–child relationship. Two self-regulatory abilities were considered: task attentiveness and emotional regulation. Associations between domain-specific qualities of childcare and self-regulation were investigated in linear regression analyses adjusted for confounding, with imputation for missing data. Results: There was no association between any provider or program characteristics of care and children's task attentiveness and emotional regulation. The quality of activities in childcare were associated only with higher levels of emotional regulation at age 4-5 years (β = 0.24; 95% CI, 0.03-0.44) and 6-7 years (β = 0.26; 95% CI, 0.04-0.48). Higher-quality carer–child relationships were associated with higher levels of task attentiveness (β = 0.20; 95% CI, 0.05-0.36) and emotional regulation at age 4-5 years (β = 0.19; 95% CI, 0.04-0.34) that persisted to age 6-7 years (β = 0.26; 95% CI, 0.10-0.42; β = 0.31; 95% CI, 0.16-0.47). Conclusion: Among children using formal childcare, those who experienced higher-quality relationships were better able to regulate their attention and emotions as they started school. Higher emotional regulation was also observed for children engaged in more activities in childcare. Beneficial effects were stable over time.
The Journal of Pediatrics
Keywords: Child Development -- Behaviour; Children -- Early childhood; Child Care; Childhood and child development; Child Care; Child Development; Children; Early childhood; Behaviour; Childhood and child development